Sistem Informasi Pengelolaan Deposit Bola Golf Berbasis Website - Andi Nurkholis; Iwan Syahputra; Temi Ardiansah (CV. Keranjang Teknologi Media, 2023)
Rizki Golf Driving Range is a driving range that provides facilities according to the needs of visitors, there is a system that is done manually, namely managing golf ball deposit funds. The data management process still uses ledgers and members must come directly to the Rizki Golf Driving Range to make deposits and the calculations are still done conventionally using a calculator and the data is stored in archive form. extreme programming development method and will be implemented using the PHP programming language and MySQL as the database. This system will be tested using ISO 25010. The results of this study are the stages in managing deposit data so that it can assist in decision making. With several differences in this study, namely using a system that can see the remaining deposits per member and complete information about deposit funds made online. with a total average of 91.01%.